2017
DOI: 10.1016/j.aott.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting lifespan following below-knee amputation in diabetic patients

Abstract: IntroductionUntreatable foot problems in diabetics may require lower extremity amputation, which has a high level of patient mortality. This high mortality rate is worse than most malignancies. The present study aimed to identify parameters that can be used to estimate survival in DM patients undergoing below-knee amputations for diabetic foot problems.Materials and methodsA total of 470 patients (299 males, 171 females) with a mean age of 64.32 years who underwent below-knee amputation for diabetic foot probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 33 publications
(39 reference statements)
2
35
2
3
Order By: Relevance
“…Those results agree with ours, showing that chronic renal disease, with or without dialysis, increases the risk of dying aside from the level of amputation. Beyaz et al reported that hemo-dialysis increases mortality by 1.53 times (95% CI, 1.218–1.936) among diabetic patients undergoing below-knee amputations [54].…”
Section: Discussionmentioning
confidence: 99%
“…Those results agree with ours, showing that chronic renal disease, with or without dialysis, increases the risk of dying aside from the level of amputation. Beyaz et al reported that hemo-dialysis increases mortality by 1.53 times (95% CI, 1.218–1.936) among diabetic patients undergoing below-knee amputations [54].…”
Section: Discussionmentioning
confidence: 99%
“…Although men undergo more non-traumatic, vascular-related amputations of the lower extremities, women are usually more severely ill and affected at a more advanced age [6]. It is underappreciated that women tend to have a significantly shorter (1.38 times) post-operative lifetime (95% CI, 1.11-1.72, p = 0.04) after below-the-knee amputation [2]. In 2013, we reported a benefit of edetate disodium-based therapy in patients with a prior myocardial infarction (MI) [7].…”
Section: Discussionmentioning
confidence: 99%
“…Critical limb ischemia (CLI) carries a mortality rate of 24% at one year and 54-60% at five years, a mortality more severe than most cancers [1]. It is underappreciated that women undergoing amputation for CLI are older, more severely ill, and have a poorer prognosis than men [2]. Epidemiological studies have shown an association between environmentally acquired vasculotoxic metals, coronary events, and peripheral artery disease [3-5].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of limb amputation in diabetic patients is 15 to 20 times higher than that in non-diabetic individuals, reaching even 15% [1,2]. Overall mortality after amputation ranges from 13-40% at 1 year, 35-65% at 3 years, and 39-80% at 5 years [3].…”
Section: Introductionmentioning
confidence: 99%